An Exploratory Study Of Blind And Visually Impaired Persons As Professional Interpreters - Shuaa Alamri; Mohammed Albarakati; Mohammed Alshahrani (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study explores the cognitive abilities of blind and visually impaired individuals in relation to their potential to perform interpreting tasks, addressing a notable gap in the existing literature. While prior research has examined interpreter competencies and disability studies separately, few empirical investigations have focused on the aptitude of visually impaired individuals for cognitively demanding tasks such as interpreting. This research seeks to bridge that gap by empirically examining the cognitive strengths of this group- particularly in memory, attention, and language- thereby challenging prevailing assumptions and promoting inclusivity within the interpreting profession. It seeks to specifically investigate (1) the extent to which blind and visually impaired individuals demonstrate memory capacities aligned with the competences required in interpreting, and (2) how blindness influences interpreters’ cognitive and professional performance. Data were collected from 32 Saudi secondary school students (18 male, 14 female) with varying degrees of visual impairment. A modified version of the Montreal Cognitive Assessment – Blind version (MoCA-Blind) was administered to assess three auditory-based domains: Memory (Delayed Recall), Attention, and Language. The findings indicate that visually impaired students- particularly females- demonstrate strong and consistent cognitive performance in memory, attention, and language, which are essential for effective simultaneous interpreting.